DNA compaction and dynamic observation in a nanopore gated sub-attoliter silicon nanocavity. Issue 33 (9th August 2022) - Zeng, Shuangshuang; Chinappi, Mauro; Cecconi, Fabio; Odijk, Theo; Zhang, Zhen
Abstract : We present a nanopore gated sub-attoliter silicon nanocavity device. It allows compaction of single DNA molecules under certain conditions and the dynamic fluctuations of the compacted DNA can be monitored in real time. Abstract : Confinement of biopolymers inside volumes with micro- or nanoscale lateral dimensions is ubiquitous in nature. Investigating the behavior of biopolymers in a confined environment is essential to improve our basic understanding in life sciences. In this work, we present a nanopore gated sub-attoliter silicon nanocavity device, which allows DNA compaction similar to that in virus capsids. Single DNA molecules can be electrically driven into the nanocavity, and then get compacted inside the nanocavity under certain conditions. The dynamic fluctuations of the compacted DNA can be monitored via ionic current measurements. The mechanism for the DNA compaction is elucidated by varying the DNA length or concentration, voltage polarity, nanocavity dimensions and ionic strength. Furthermore, Brownian dynamics simulations reveal the dynamic fluctuations of the compacted DNA, which are reflected in the measured ionic current. Our nanocavity device is anticipated to provide a controlled environment in extremely small volumes for investigating the physics of confined biopolymers.